Effects of Poplar Ecological Retreat on Habitat Suitability for Migratory Birds in China’s Dongting Lake Wetland - Qu, Xinyu; Du, Chunyan; Wu, Haipeng; Xiong, Ying; Yu, Guanlong; Wang, Jiasheng; Dai, Juan; Wu, Lixue; Zhang, Zhuo; Zhu, Yuqian; Liu, Jingdu (Frontiers in Environmental Science, 2022)
Dongting Lake wetland is an important wintering place for migratory birds in the world. The introduction and large-scale planting of poplar (Populus deltoides) in this area has profoundly changed its land cover and brought huge potential ecological risks. The Poplar Ecological Retreat (PER) project is an important measure in response to China's ecological civilization construction policy, which aims to restore the natural state of Dongting Lake wetland, and has been widely concerned by society and scholars. However, the impact of PER on migratory bird habitats in Dongting Lake wetland has not been evaluated. In this paper, we used the method of habitat suitability modeling based on remote sensing to explore the impact of PER on the four mainly migratory bird guilds (Anatidae, Charadriidae, Ardeidae and Laridae) in Dongting Lake wetland. The results showed that the area of poplars in Dongting Lake wetland decreased significantly after PER implemented. There was a negative correlation between poplar area and moderate grade habitat area of Anatidae and Ardeidae, and a positive correlation between poplar area and general grade habitat area. However, there was no significant change in the habitat area of different grades of Charadriidae and Laridae after PER. Thus, PER improved the habitat suitability of Anatidae and Ardeidae, but had no significant effect on the habitat suitability of Charadriidae and Laridae. These conclusions can provide reference for understanding the living conditions of Dongting Lake wetland waterfowl, determining the priority protection areas and maintaining wetland biodiversity.